Praxishandbuch Forschungsdatenmanagement - Neuroth, Heike 1966- (De Gruyter Praxishandbuch, 2021)
The creation of the German National Research Data Infrastructure and the European Open Science Cloud is presenting the providers and users of research data with technical, legal, and organizational challenges. This thematically structured practical handbook looks at these challenges and provides researchers and CIOs as well as employees in institutions like libraries and computing centers with the necessary knowledge of research data management